Profile of infliximab in the treatment of pediatric Crohn’s disease - Kierus J; Szymanska E; Oracz G; Wiernicka A; Dadalski M (Dove Medical Press, 2015)
Jaroslaw Kierkus,1 Edyta Szymanska,2 Grzegorz Oracz,1 Anna Wiernicka,1 Maciej Dadalski1 1Department of Gastroenterology, Hepatology, Feeding Disorders and Pediatrics, 2Department of Pediatrics, Nutrition and Metabolic Disorders, The Children’s Memorial Health Institute, Warsaw, Poland Abstract: In recent years, a novel biologic therapy with monoclonal antibodies against tumor necrosis factor-alpha has revolutionized the treatment of Crohn’s disease. Infliximab, the first biologic agent, has been demonstrated to considerably improve both clinical and endoscopic outcomes. In view of the growing popularity of infliximab in the management of Crohn’s disease, we review the profile of the agent in the treatment of this disease in a pediatric setting. Keywords: infliximab, Crohn’s disease, children, biologic therapy, anti-TNF-agents